2019
DOI: 10.1108/mrr-10-2018-0386
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of cultural intelligence to the interaction involvement and performance of call center agents in cross-cultural communication

Abstract: Purpose This paper aims to investigate the contribution of cultural intelligence (CQ) to the interaction involvement and job performance of call center agents in the Philippines. Design/methodology/approach Data were collected from 213 call center agents from five business process outsourcing firms in the Philippines. Partial least squares structural equation modeling was used for data analysis. Findings CQ was found to be positively associated with the quality of interaction involvement and job performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 64 publications
4
28
1
3
Order By: Relevance
“…SeIain fenomena yang terjadi di atas, daIam peneIitian-peneIitian sebeIumnya masih terdapat perbedaan hasiI peneIitian antara pengaruh kecerdasan emosionaI, budaya"kerja dan kepuasan kerja terhadap"kinerja Karyawan. PeneIitian yang diIakukan oIeh (Puyod & CharoensukmongkoI, 2019) dan (Kumari & Singh, 2018) budaya berpengaruh positif terhadap kinerja. (Desky, 2014) serta (Zukarnaen et aI., 2020) juga menguatkan bahwa"budaya dan kepuasan berpengaruh terhadap kinerja karyawan.…”
unclassified
“…SeIain fenomena yang terjadi di atas, daIam peneIitian-peneIitian sebeIumnya masih terdapat perbedaan hasiI peneIitian antara pengaruh kecerdasan emosionaI, budaya"kerja dan kepuasan kerja terhadap"kinerja Karyawan. PeneIitian yang diIakukan oIeh (Puyod & CharoensukmongkoI, 2019) dan (Kumari & Singh, 2018) budaya berpengaruh positif terhadap kinerja. (Desky, 2014) serta (Zukarnaen et aI., 2020) juga menguatkan bahwa"budaya dan kepuasan berpengaruh terhadap kinerja karyawan.…”
unclassified
“…For example, Van Dyne et al (2009) and Ward et al (2008) demonstrate that the correlations between metacognitive and motivational CQ and between metacognitive and behavioral CQ are far above .7. The studies conducted by Tarique and Takeuchi (2008) and Puyod and Charoensukmongkol (2019) also report significantly high correlations among all four CQ dimensions. Bücker et al (2015: 263) suggest that high correlations among CQ dimensions “might potentially cause multicollinearity issues when assessing the effects of these dimensions on performance measures.” Many scholars have consequently treated CQ as an aggregation of all four CQ dimensions instead of disaggregating them into separated facets (Imai and Gelfand, 2010; Jiang et al, 2018; Rockstuhl et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 80%
“…CQ has been found to enhance individuals’ effectiveness in various aspects, such as communicating with foreigners (Bücker et al, 2014; Chen et al, 2011; Huff et al, 2014; Puyod and Charoensukmongkol, 2019). CQ promotes the professional achievement and psychological wellbeing of people working in foreign countries (Le et al, 2018), and has also been found to be effective in predicting individuals’ cross-cultural leadership effectiveness (Hamidianpour et al, 2016; Solomon and Steyn, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…HRM practices of firms in GS economies have different propensities to change. Prior researchers have noted that the pressures to introduce modern HRM practices are especially felt by technology industry sectors such as call-centers (Puyod and Charoensukmongkol, 2019). This can be attributed to several factors, inter alia, job pressures, lack of promotions, working time and work-life balance.…”
Section: Literature Reviewmentioning
confidence: 99%